Level of knowledge about informed consent in health care, in doctors at an essalud hospital, Chiclayo-Peru - Jara Romero, Luis Enrique (2023)
Introduction: Informed consent respects the autonomy and will of the patient, and it is the duty of the physician to guide this process. The objective of the study was: to determine the level of knowledge about informed consent in health care, in doctors from Hospital I Naylamp - EsSalud, Chiclayo March - October 2018. The study: Quantitative, descriptive, cross-sectional. A validated survey on the level of knowledge of informed consent was applied to 59 attending physicians of Hospital I Naylamp between March and October 2018. Findings: 78% were men, 55.9% between 45 and 60 years of age; 72.9% came from a public university. High level of knowledge: 35.1% of clinical physicians and 40.9% of surgical physicians; 51.7% in doctors with 10 and 20 years of service and 71.4% of doctors with a doctorate degree. Conclusions: An average of 12.95 was obtained, the average level of knowledge about informed consent in medical practice.